NMDA Receptor Antagonists for Treatment of Depression - Zeynep Ates-Alagoz; Adeboye Adejare (MDPI AG, 2013)
Depression is a psychiatric disorder that affects millions of people worldwide. Individuals battling this disorder commonly experience high rates of relapse, persistent residual symptoms, functional impairment, and diminished well-being. Medications have important utility in stabilizing moods and daily functions of many individuals. However, only one third of patients had considerable improvement with a standard antidepressant after 2 months and all patients had to deal with numerous side effects. The N-methyl-d-aspartate (NMDA) receptor family has received special attention because of its critical role in psychiatric disorders. Direct targeting of the NMDA receptor could result in more rapid antidepressant effects. Antidepressant-like effects of NMDA receptor antagonists have been demonstrated in different animal models. MK-801 (a use-dependent channel blocker), and CGP 37849 (an NMDA receptor antagonist) have shown antidepressant properties in preclinical studies, either alone or combined with traditional antidepressants. A recent development is use of ketamine clinically for refractory depression. The purpose of this review is to examine and analyze current literature on the role of NMDA receptor antagonists for treatment of depression and whether this is a feasible route in drug discovery.